O crime de quadrilha ou bando à luz da teoria do bem-jurídico penal - Barrilari, Claudia Cristina (2008)
The highlight currently given to danger crimes, allied to the organize criminality increase, are strong triggering factors of the focus received by gang crimes at the current moment. The caselaw analysis of the mentioned criminal offense makes it possible to conclude that incriminations due to gangs has been vulgarized , in order to proliferate denounces due to gang that do not culminate or should not culminate in conviction, as the strict occurrence of their normative elements. The offense type, either for being open or for prescinding material results, assumed an evident secondary plan, which cause an evident unbalance in the criminal law fundamental principles compliance. Thus, we intend to conduct the present work analyzing those two factors, danger crimes and criminal association, and the consequences derived from, of the one side, leaving the punitive legitimacy aside, with the criminal law assuming an eminently social control function; of the other side, it is sought the gang crime legitimacy and the adequate dogmatic use of danger crimes, supported by the guaranty criminal law, guided by the human being maximum protection. The topic is arduous, mainly in face of the violence escalation, a phenomenon of the current times. Maybe the current jurist concern should be to conciliate the human person defense, in its strictest acceptation since Enlightenment, with the criminal treatment hardening as an appropriate mechanism for violence containment. The risk increment to which the current society is exposed cannot be despised. Violence assumes varied forms, and it is in this context that the criminal advance relief is verified, as an attempt to contain crime at its embryonary moment. In crimes of diffuse objectivity, the advance relief is potentialized based on the belief that this is the only way to effectively protect the juridical stead. At the other end, what is fought is the damage verification in a diffuse way, the relation between a crime and a determined victim is replaced with collective or even undetermined victimization. The magnitude generated by the involved interest or by the possibility of affecting innumerous victims requires the maximum protection of the stead, so that, in the name of an illusory efficiency, it be compatible only with advance relief up to the limit at which the protected stead is not under any risk threat. This can be verified in certain environmental crimes, for instance. The main issue consists in finding a balance point, that is, in discovering as from which moment the criminal advance relief actuation, especially in reference to gang crimes. This question is directly related to the classic conception of criminal law as the normative system ultima ratio